(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
Puerperal sepsis is an important cause of maternal morbidity and mortality in developing countries. This study was undertaken to isolate and identify the Aerobic bacterial agents of Puerperal sepsis among the patients admitted in Mymensingh Medical College Hospital during the period from July, 2006 to June, 2007. Endocervical swabs/secretions were collected from 50 cases of Puerperal sepsis and were cultured aerobically. Out of 50 samples, 42 (84%) yielded growth in cultures. Among 42 culture positive cases, 20 (40%) were Aerobic organisms and 22 (44%) were mixed, i.e., Aerobic and Anaerobic bacteria. The isolated Aerobic organisms were Staphylococcus aureus (26, 61.90%), Escherichia coli (6, 14.28%), Staphylococcus epidermidis (5, 11.90%), Streptococcus pyogenes (3, 7.14%) and Enterococcus faecalis (2, 4.76%). The organisms were identified by standard biochemical tests. All isolates of S.aureus and S. epidermidis were sensitive to Cephalexin and Vancomycin. Similarly all the strains of E. coli were sensitive to Gentamicin, Amikacin, Ciprofloxacin and Cephalexin. All the strains of S. pyogenes were sensitive to Amoxicillin and all the isolates of Enterococcus were sensitive to Amoxicillin and Cephalexin. Bangladesh J Med Microbiol 2008; 02 (01): 22-27 DOI:http://dx.doi.org/10.3329/bjmm.v2i1.21785